Optimalisasi Komposisi Bio-Ink Berbasis Ekstrak Bunga Telang (Clitoria ternatea) dan Gum Arabic Terhadap Capaian Warna Cyan pada Aplikasi Inkjet Printing - Salsabila, Salsabila; Kusumantoro, Heribertus Rudi; Pratama, Yoga Putra (Fakultas Teknik UMSU, 2025)
The digital printing industry currently faces environmental challenges due to the use of synthetic inks containing hazardous chemical compounds. This study aims to optimize the composition of bio-ink based on butterfly pea flower extract (Clitoria ternatea) and gum arabic as an environmentally friendly alternative for cyan ink in inkjet printing applications. The research method used varying concentrations of butterfly pea flower extract (1%, 3%, 5%, and 7%) and gum arabic (1%, 2%, 3%, and 4%) with testing parameters of pH, viscosity, and color analysis using the CIE Lab system and Delta E (ΔE) evaluation. The results showed that all formulations produced pH in the range of 5.3-6.6, suitable for inkjet printing applications. Viscosity values ranged from 7.57-9.35 mPa.s, meeting technical standards for inkjet ink (2-10 mPa.s). Color analysis showed that the formulation of 7% butterfly pea flower with 2% gum arabic produced the lowest ΔE value (14.55), indicating the highest similarity to commercial cyan ink. Statistical analysis confirmed that butterfly pea flower concentration significantly influenced pH and color accuracy (p-value 0.05). This research successfully developed sustainable bio-ink with physicochemical characteristics approaching commercial ink standards, contributing to the development of environmentally friendly printing industry.